The Challenges Of Implementing Medical Practice In The Artificial Intelligence Era - Yuliana Yuliana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This paper aims to describe the challenges of healthcare practice in the artificial intelligence era. This is a narrative literature review. Literature was searched from Science Direct, Google Scholar, and PubMed. The inclusion criteria are research and review. The exclusion criteria are unavailable in full-text journals. Artificial intelligence (AI) is applied in large activities of daily life. However, besides the positive sides of AI, there are still many concerns about implementing AI in medical practice and healthcare services. The sources of the problems are uneasiness at the beginning, lack of understanding, the position of the physicians and patients, the decision-making process, reliability of the data, and accountability. AI has some gaps in handling the privacy of the data. On the other side, the system should be updated for monitoring functions. Therefore, the challenge in implementing AI in the healthcare practice is the integrated work of the AI developer, clinicians, regulators, and researchers. This paper is a narrative literature review, therefore the information would not be as complete as a research study. The contribution of the paper is to the healthcare practice and research development in artificial intelligence. Novelty: This paper includes the development and challenges of artificial intelligence in medical science and healthcare practice.